Estimation Metabolic Status in High Yielding Dairy Cows During Transition Period and Full Lactation - Djokovic, Radojica; Cincovic, Marko; Ilic, Zoran; Kurcubic, Vladimir; Andjelic, Biljana; Petrovic, Milos; Lalic, Nebojsa; Jasovic, Boban (Acta Scientiae Veterinariae, 2019)
Background: Major changes in the metabolic functions in high-yielding dairy cows occur during the transitional period and during lactation. Parturition and lactogenesis are accompanied by many physiological changes that facilitate the maintenance of homeostasis Consequently, physiological situations leading to a negative energy balance are coupled to an increased uncontrolled rate of body fat mobilisation and the increased fatty acids accumulation in hepatocytes and blood ketone bodies, resulting in disturbances of the morphological and physiological liver integrity. The objective of the present study was to estimate metabolic status in late pregnant, early lactation and full lactation Holstein dairy cows on the basis changes of blood concentrations of selected biochemical markers. Materials, Methods & Results: The experiment included 36 Holstein cows. Three groups of clinically healthy cows were chosen from the herd. Group 1 consisted of late pregnant cows (n = 12) from 30 to 1 day (20 ± 15) to partus; Group 2 comprised early lactation cows (n = 12) in the first month of lactation (15 ± 12 days), and Group 3 included full lactation cows (n = 12) between 60 to 90 days of lactation (81 ± 30 days). Blood samples were collected from all cows, by punction of the jugular vein. Biochemical testing for markers in the blood serum showed significantly lower values (P < 0.05) of glucose, TG, Tchol. and urea in early cows than in full lactation and late-pregnant cows. The blood concentration of NEFA and BHB was significantly increased (P < 0.05) in the group of cows in early lactation compared to the other groups of cows. The mean tBIL. concentration and the serum AST, GGT and ALT activities were markedly increased (P < 0.01) in the lactation cows compared to the late pregnant cows. Furthermore, the intensity of lipomobilisation (NEFA or BHB concentrations) correlated positively (P < 0.05) with the markers of cell damage or liver function impairment (tBIL., serum AST, ALT and GGT activities), but negatively (P < 0.05) with the circulating concentrations of compounds synthesised in liver (glucose, TG and urea). Discussion: In dairy cows, it was observed that up to 50 % of females exhibited some lipid accumulation in liver in the first 3 weeks after calving and that fatty liver occurs primarily in this period. Liver can be categorized into mild, moderate and severe fatty liver as dependent on the degree of pathology and a mild fatty infiltration of liver in dairy cows during lactation is considered to be almost physiological. The blood BHB and NEFA concentrations are markers of lipomobilisation and positively associated with the ketosis and liver steatosis intensity. The simultaneous and parallel variations observed between the extent of the fat infiltration in liver and the serum BHB and NEFA concentrations in puerperal cows clearly indicated that the intense lipomobilisation in the post-partum period has induced lipid overloading and ketogenesis in the liver. On the other hand, it was observed significant decreases in the serum biochemical markers, at least partially synthesised in the liver, such as glucose, TG, Tchol., urea, albumin and TP during the postpartum period. However, the liver steatosis has induced some cellular lesions as evidenced by significant increases in the serum tBIL. concentrations and in the AST, ALT, GGT and LDH enzyme activities in puerperal cows. All these biochemical metabolites may be used as important biochemical markers in the determination of the metabolic status in high-yielding dairy cows during the transition period and during lactation.